A novel comparison of energy-exergy, and sustainability analysis for biomass-fueled solid oxide fuel cell integrated gas turbine hybrid configuration. (1st May 2023) - Sinha, Abhinav Anand; Saini, Gaurav; Sanjay,; Shukla, Anoop Kumar; Ansari, Mohd. Zahid; Dwivedi, Gaurav; Choudhary, Tushar
Graphical abstract: Highlights: A novel comparison of pine sawdust, poplar sawdust and almond shell for SOFC-GT hybrid system. Exergy analysis for each component is compared with the three proposed biomass. Eight modified dimensionless exergy indicator is used for performance comparison. Pine sawdust has the maximum thermal efficiency of 63.12% at rp = 6 and TIT = 1250 K. Abstract: Conventional gas turbines (GT) are working with limited fuels and exhibit thermal efficiency between 30 and 40%. This restriction with the fuels and its efficiency range can be improved by adding an electrochemical fuel cell, i.e; a Solid Oxide Fuel Cell (SOFC). This paper proposes three different types of biomasses, including pine sawdust, poplar sawdust, and almond shell, which may all be used to power the novel biomass-fueled solid oxide fuel cell gas turbine (SOFC-GT) presented herein. MATLAB based simulation is used to validate the results of this fuel cell based hybrid cycle performance. Three performance parameters are considered namely, current density (id ), turbine input temperature (TIT), and pressure ratio (rp) to evaluate the performance of the proposed system. For this, energy-exergy approaches based on the first and second law of thermodynamics are used to assess each cycle component as well as the entire system. The sustainability index and environmental impact factor of each component are evaluated using dimensionless modified exergy indicators. With all three of the suggested biomass fuels, the SOFC-GT hybrid system runs most effectively at pressure-ratio of 6 and TIT 1250 K. Pine sawdust (Case-1) exhibits the largest levels of exergy destruction (2653.14 kW), environmental effect (0.91), and the lowest sustainability index (2.09) but it also has the highest levels of thermal efficiency (63.12%).